Age-Dependent Changes in Synaptic NMDA Receptor Composition in Adult Human Cortical Neurons - Chrysia M. Pegasiou; Ardalan Zolnourian; Diego Gómez‐Nicola; Katrin Deinhardt; James A. R. Nicoll; Aminul I. Ahmed; Girish Vajramani; Paul Grundy; Matthijs B Verhoog; Huibert D. Mansvelder; V. Hugh Perry; Diederik Bulters; et al. (2020)
Abstract The molecular processes underlying the aging-related decline in cognitive performance and memory observed in humans are poorly understood. Studies in rodents have shown a decrease in N-methyl-D-aspartate receptors (NMDARs) that contain the GluN2B subunit in aging synapses, and this decrease is correlated with impaired memory functions. However, the age-dependent contribution of GluN2B-containing receptors to synaptic transmission in human cortical synapses has not been previously studied. We investigated the synaptic contribution of GluN2A and GluN2B-containing NMDARs in adult human neurons using fresh nonpathological temporal cortical tissue resected during neurosurgical procedures. The tissue we obtained fulfilled quality criteria by the absence of inflammation markers and proteomic degradation. We show an age-dependent decline in the NMDA/AMPA receptor ratio in adult human temporal cortical synapses. We demonstrate that GluN2B-containing NMDA receptors contribute to synaptic responses in the adult human brain with a reduced contribution in older individuals. With previous evidence demonstrating the critical role of synaptic GluN2B in regulating synaptic strength and memory storage in mice, this progressive reduction of GluN2B in the human brain during aging may underlie a molecular mechanism in the age-related decline in cognitive abilities and memory observed in humans.